Meckel's diverticulum causing simultaneous hemoperitoneum and hematochezia - James G. Glasser, MD, FACS (Elsevier, 2021)
In this report, a case is presented in which a Meckel's Diverticulum causes simultaneous bright red, rectal bleeding and intraperitoneal bleeding. The first manifestation is typical; the second is highly unusual.A general discussion of Meckel diverticulum follows this case presentation, emphasizing the variety and heterogeneity of this anomaly.